Formulation and characterization of risperidone nanocrystals for enhanced solubility and dissolution - M. Subramani; R. Arulkumar; P. Manikandan; P. K. Varshini; S. Mounisha (Creative Pharma Assent, 2026)
Background: Risperidone (RIS) is categorized as a BCS Class II antipsychotic and exhibits poor water solubility and a slow dissolution rate, which restricts its therapeutic effectiveness. The present study aims to formulate RIS nanocrystals to overcome pharmaceutical challenges and improve their solubility. Methodology: Nanosuspensions of RIS were prepared using high-speed homogenization, with different polymer ratios. The physicochemical properties were characterized using FTIR, SEM, particle size analysis, zeta potential measurement, X-ray powder diffraction, entrapment efficiency evaluation, drug content analysis, and in vitro release testing. Direct compression was used to manufacture tablets from the optimized nanocrystals, and their dissolution performance was assessed against conventional RIS tablets. Results and Discussion: The formulation F7, containing 0.1% Poloxamer 188 and prepared at 25,000 rpm, exhibited the optimal particle size (78.62 nm), PDI (0.223), and zeta potential (-18.9 mV), and the SEM images revealed needle-shaped crystals. Entrapment efficiency was 86.22±1.61% with a drug content of 67.885±2.02%. The F7 nanosuspension released 90.23±1.91% of the drug in phosphate buffer (pH 6.8) within 60 minutes. Reducing the size of nanoscale particles enhanced their surface area, hence increasing their solubility. The F7 nanocrystal tablets released 86.28±1.83% of the drug, whereas the conventional tablets released 77.51±2.15%. This data demonstrates that this method is more effective. Conclusion: RIS nanocrystals were developed to enhance solubility and accelerate dissolution rates. The F7 formulation exhibited enhanced stability and improved release, suggesting its potential to optimize oral medication delivery.